Publisher Correction: Clinical outcomes and quality of life of patients after surgical treatment of a tibia plateau fracture...Höller LF, Höller S, Klinger E, et al. European Journal of Trauma & Emergency Surgery. 2025;51(1):1-8. - Höller, Lina F.; Höller, Sebastian; Klinger, Elias; Henkies, Danny; Leha, Andreas; Lehmann, Wolfgang; Dobroniak, Corinna C.; Hoffmann, Daniel B. (European Journal of Trauma & Emergency Surgery, 2026)
This publisher correction addresses a typesetting error in the display of Figure 1 in an article originally published on 28 October 2025. The error affected only the PDF version, while the online version remained accurate. The correction has been made, and the publisher has issued an apology for the mistake. Springer Nature also states its neutrality regarding jurisdictional claims in published maps and institutional affiliations.